1991
DOI: 10.1210/jcem-72-6-1359
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Control of Pituitary Hormone Secretion in Early Human Pregnancy*

Abstract: To determine the influence of ovarian relaxin on the secretion of pituitary GH and PRL in vivo, we evaluated circulating serum hormone levels in 17 pregnant patients with functional corpora lutea (group I) and compared them to levels in 10 patients with premature ovarian failure (POF; group II) who became pregnant with egg donation and did not have corpora lutea. Group II patients had exogenous hormonal support. Serum relaxin (RLX), GH, PRL, estradiol (E2), and progesterone levels were measured weekly by RIA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 10 publications
0
18
0
2
Order By: Relevance
“…The hypothesis can only be fully disproved if an increase in circulating concentrations of relaxin fails to initiate an increase in PP14 in early pregnancy. However, women with absent ovarian function who achieve a pregnancy after ovum donation and exogenous steroid support have neglible serum PP14 and relaxin levels in early gestation (Emmi et al 1991, Johnson et al 1991, Critchley et al 1992. A recent report (Johnson et al 1993) described depressed levels of PP14 in the first trimester of 'clomiphene pregnancies'; these findings clearly show that the synthesis and release of PP14 by the endometrium in early pregnancy is a result of complex interactions between the endometrium and the corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis can only be fully disproved if an increase in circulating concentrations of relaxin fails to initiate an increase in PP14 in early pregnancy. However, women with absent ovarian function who achieve a pregnancy after ovum donation and exogenous steroid support have neglible serum PP14 and relaxin levels in early gestation (Emmi et al 1991, Johnson et al 1991, Critchley et al 1992. A recent report (Johnson et al 1993) described depressed levels of PP14 in the first trimester of 'clomiphene pregnancies'; these findings clearly show that the synthesis and release of PP14 by the endometrium in early pregnancy is a result of complex interactions between the endometrium and the corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
“…The relaxin profile during non-conceptive and early in conceptive cycles (Stewart et al 1990) and the published profiles of PP14 levels are very similar Qulkunen et af 1985, 1986, HoweU et al 1989 both in terms of timing and the magnitude of the rise in early gestation. Relaxin is, however, absent in serum when egg donation permits conception in agonadal women (Emmi et al 1991, Johnson et al 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Second, circulating relaxin levels are often much lower than blood or tissue levels within specific organs [48]. Third, circulating relaxin levels in steroid hormone supplemented patients undergoing ovum donation cycles remain below the limits of detection despite successful pregnancy [49]. Non-human primates subjected to ovariectomy also maintain pregnancy when supplemented with steroid hormones [48,50].…”
Section: Ovarian Relaxin Secretion and Functional Regulationmentioning
confidence: 99%
“…That ovarian relaxin is not required for successful term pregnancy in primates is suggested by several independent lines of clinical and experimental evidence indicating that pregnancies can be initiated and maintained: (i) in humans with premature ovarian failure, a sub population of infertility patients who fail to develop a corpus luteum and, presumably, ovarian relaxin [49], (ii) in baboons subjected to unilateral removal of the corpus luteum bearing ovary following establishment of a functional placenta [48], (iii) in macaques subjected to bilateral ovariectomy at embryo transfer, prior to establishment of a placenta [50] and (iv) in marmosets subjected to prostaglandin F2α-mediated luteolysis in mid-pregnancy [51]. The results of these studies indicate that pregnancies can be maintained in the absence of a functional luteal phase ovary provided that steroid hormone supplementation is provided.…”
Section: Ovarian Relaxin Secretion and Functional Regulationmentioning
confidence: 99%
“…Support for a relaxin role in implantation was provided by Stewart et al (16), who showed that relaxin levels were significantly impaired in women with early pregnancy loss and that granulosa cell production of relaxin was predictive of pregnancy outcome in IVF patients (17). However, substantial experimental data have suggested that circulating levels of relaxin may not explain the full biologic impact of this hormone: Circulating relaxin levels in steroid hormone supplemented patients undergoing ovum donation cycles remain below the limits of detection despite successful pregnancy (18) and nonhuman primates subjected to ovariectomy also maintain pregnancy when supplemented with steroid hormones (19). Taken together, these observations show that the primate ovary may be the major source of relaxin, but that high levels of circulating relaxin may not be necessary for embryo implantation in primates.…”
mentioning
confidence: 99%